2020
DOI: 10.1186/s40885-020-00153-z
|View full text |Cite
|
Sign up to set email alerts
|

Intensive blood pressure lowering: a practical review

Abstract: According to the last Hypertension guideline recommendations, it may be concluded that intensive BP lowering is only advisable in a subgroup of patients where there is a clear net benefit of targeting to lower BP goals. However, taking into account the relevance of correct BP measurement, estimates of the benefits versus the harm should be based on reliable office BP measurements and home BP measurements. There is still debate about which BP goals are optimal in reducing morbidity and mortality in uncomplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Beside these phenotypic characteristics of hypertension in elderly subjects, this population presents some other relevant problems. One of them is that the available evidence on the efficacy and safety of BP lowering treatment in these patients is scarce [36].…”
Section: Other Aspects Related To Abpm In Elderlymentioning
confidence: 99%
“…Beside these phenotypic characteristics of hypertension in elderly subjects, this population presents some other relevant problems. One of them is that the available evidence on the efficacy and safety of BP lowering treatment in these patients is scarce [36].…”
Section: Other Aspects Related To Abpm In Elderlymentioning
confidence: 99%
“…Based on studies conducted by the SPLINT trial ( 2 ) and ACCORD trial ( 3 ), strict BP control shows better cardiovascular (CV) outcomes, forcing physicians to set stricter target BPs in the treatment of HBP ( 4 ). Therefore the importance of obtaining reliable BP readings in patients with hypertension and comorbidities ( 5 ). For this reason, the 2017 ACC/AHA Guidelines recommended lowering the existing threshold BP target from 140/90 mmHg to less than 130/80 mmHg ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is an important risk factor for cardiovascular and cerebrovascular events [ 1 ], and the number of patients with hypertension has steadily increased to more than 12 million in Korea [ 2 ]. Recently, although clinical trials and meta-analyses have strongly suggested intensive blood pressure (BP) lowering in patients with hypertension [ 3 ], approximately 1%–2% of patients eventually develop a severe acute increase in BP [ 4 ]. Hypertensive crisis or severe hypertension is defined as a BP elevation above 180 mmHg for systolic BP (SBP) and/or above 110–120 mmHg for diastolic blood pressure (DBP) according to the international practice guidelines for hypertension [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%